Targeting of ribosomal protein S6 to dendritic spines by in vivo high frequency stimulation to induce long-term potentiation in the dentate gyrus - Nihonmatsu, Itsuko (Biol Open, 2015)
Late phase long-term potentiation (L-LTP) in the hippocampus is believed to be the cellular basis of long-term memory. Protein synthesis is required for persistent forms of synaptic plasticity, including L-LTP. Neural activity is thought to enhance local protein synthesis in dendrites, and one of the mechanisms required to induce or maintain the long-lasting synaptic plasticity is protein translation in the dendrites. One regulator of translational processes is ribosomal protein S6 (rpS6), a component of the small 40S ribosomal subunit. Although polyribosomes containing rpS6 are observed in dendritic spines, it remains unclear whether L-LTP induction triggers selective targeting of the translational machinery to activated synapses in vivo. Therefore, we investigated synaptic targeting of the translational machinery by observing rpS6 immunoreactivity during high frequency stimulation (HFS) for L-LTP induction in vivo. Immunoelectron microscopic analysis revealed a selective but transient increase in rpS6 immunoreactivity occurring as early as 15 min after the onset of HFS in dendritic spine heads at synaptic sites receiving HFS. Concurrently, levels of the rpS6 protein rapidly declined in somata of granule cells, as determined using immunofluorescence microscopy. These results suggest that the translational machinery is rapidly targeted to activated spines and that this targeting mechanism may contribute to the establishment of L-LTP.